Justice Collaborator’s Position and Function on Witness Protection’s Rights as a Suspect from the Perspective of Criminal Law in Indonesia - Norhaiden Unsil; Ema Mar’ati Sholecha; Ahmat Saiful; Sheilla Yunika; Hariyanto Hariyanto (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
To handle a specific criminal act, a justice collaborator is greatly required. The concept and term of justice collaborator is something new in Indonesia. This method is practically used to eradicate an organized crime. Both conceptual and statutory approaches were used in this research. Juridical-normative techniques were implemented to descriptively explain the existing problems. This research aimed to deeply and conceptually examine justice collaborator’s position and function in the perspective of Human Rights to protect and provide special treatments to the main actors in cooperating with law enforcement officials (justice collaborators) against an organized crime. The position of justice collaborator either as a witness or suspect to provide information in court and then used as a judge's consideration is to mitigate the sentence to be imposed. This collaboration can provide various benefits, so that law enforcement officials can fight against serious criminal acts. Thus, a justice collaborator has a specific rule (lex specialis derogerat lex generalis) to guide law enforcers, such as police officers, prosecutors, and judges to uncover a specific crime committed by a syndicate deliberately violating laws in very systematic and organized ways.